Increased risk of miscarriage among women experiencing physical or sexual intimate partner violence during pregnancy in Guatemala City, Guatemala: cross-sectional study - Hoch Jeffrey S; Samayoa Blanca E; Boivin Jean-François; Morales Rosa E; Johri Mira; Grazioso Carlos F; Barrios Matta Ingrid J; Sommen Cécile; Baide Diaz Eva L; Fong Hector R; Arathoon Eduardo G (BMC Pregnancy and Childbirth, 2011)
Abstract Background Violence against women by their male intimate partners (IPV) during pregnancy may lead to negative pregnancy outcomes. We examined the role of IPV as a potential risk factor for miscarriage in Guatemala. Our objectives were: (1) To describe the magnitude and pattern of verbal, physical and sexual violence by male intimate partners in the last 12 months (IPV) in a sample of pregnant Guatemalans; (2) To evaluate the influence of physical or sexual IPV on miscarriage as a pregnancy outcome. Methods All pregnant women reporting to the maternity of a major tertiary care public hospital in Guatemala City from June 1st to September 30th, 2006 were invited to participate in this cross-sectional study. The admitting physician assessed occurrence of miscarriage, defined as involuntary pregnancy loss up to and including 28 weeks gestation. Data on IPV, social and demographic characteristics, risk behaviours, and medical history were collected by interviewer-administered questionnaire. Laboratory testing was performed for HIV and syphilis. The relationship between IPV and miscarriage was assessed through multivariable logistic regression. Results IPV affected 18% of the 1897 pregnant Guatemalan women aged 15-47 in this sample. Verbal IPV was most common (16%), followed by physical (10%) and sexual (3%) victimisation. Different forms of IPV were often co-prevalent. Miscarriage was experienced by 10% of the sample (n = 190). After adjustment for potentially confounding factors, physical or sexual victimisation by a male intimate partner in the last 12 months was significantly associated with miscarriage (ORadj 1.1 to 2.8). Results were robust under a range of analytic assumptions. Conclusions Physical and sexual IPV is associated with miscarriage in this Guatemalan facility-based sample. Results cohere well with findings from population-based surveys. IPV should be recognised as a potential cause of miscarriage. Reproductive health services should be used to screen for spousal violence and link to assistance.